Determinants of the Adoption of the Dairy Component in Dairy-Based Integrated Farming Systems in the Coastal Region of West Bengal - Subrata Barman, Ravinder Malhotra, Udita Chaudhary, Biswajit Sen, Sanjit Maity; Ritu Chakraborty (Indian Journal of Dairy Science, 2026)
The coastal region of West Bengal is prone to environmental challenges such as cyclones, water salinity, and frequent flooding, for that reason, people prefer diversifying different farming enterprises over the specialization of any farming enterprise. A sample of 200 respondents was collected through a multi-stage random sampling method to analyse the determinants of the adoption of the dairy component in dairy-based integrated farming systems (IFSs) in coastal region of West Bengal. Employing a seemingly unrelated bivariate probit model, the study utilized the profit share of dairy in IFSs and the number of cattle in households as dependent variables (which are the adoption parameters of the dairy component in IFSs), while farmers’ socio-economic attributes served as explanatory variables. The finding shows the number of cattle in households had a positive marginal effect on the profit share of dairy in IFSs. In the Dairy + Crop + Goat framing system, the probability of more cattle adoption was low compared to the Dairy + Crop farming system. Regular extension contact by the farmers helped to get more profit from dairy component in IFSs. Most dairy farmers sold their raw milk to retailers. If farmers sell their raw milk to milk vendors, the profit share of dairy in IFSs reduction probability will be 20 per cent compared to a cooperative society. Hence, establishing more cooperative societies and expanding their area coverage in this region become crucial for adopting more dairy components in IFSs.